Persona Deicsis in The Novel Merindu Baginda Nabi Works of Habiburrahman El Shirazy A Review of Pragmatics - Fauziah, Indah; Faizah, Hasnah; Charlina, Charlina (Blantika: Multidisciplinary Journal, 2024)
Merindu Baginda Nabi is a novel by Habiburrahman El Shirazy which contains various forms of deixis in every speech event made by the perpetrator or character of the story. This research aims to describe the form and function of persona deixis in the novel Merindu Baginda Nabi by Habiburrahman El Shirazy. The method used in this research is descriptive qualitative. The data collection technique used was note-taking. The data analysis technique in this research uses descriptive techniques. The research results show that the novel Merindu Baginda Nabi by Habiburrahman El Shirazy contains various forms of persona deixis, namely: singular and plural first person deixis, singular and plural second person deixis, and singular and plural third person deixis. The singular first person deixis, namely saya, aku, -ku, and ku-, was identified in 71 data, while the plural first person deixis, namely kita, kami, and kami semua, was identified in 31 data. The singular second person deixis, namely kamu, kau, and -mu was identified in 45 data, while the plural second person deixis, namely kalian, was identified in 10 data. The singular third person deixis, namely dia, beliau, ia, and -nya was identified in 31 data, while the plural third person deixis, namely mereka was identified in 9 data. The functions of persona deixis are: 40 identified referential functions, 102 identified emotive functions, and 55 identified conative functions. The novel Merindu Baginda Nabi by Habiburrahman El Shirazy predominantly uses the form of first person singular deixis and the function of personal deixis is in the form of an emotive function because the author tends to write speech that has the role of the speaker and focuses more on the feelings or attitudes of the speaker in his speech.